Design and development a novel uranyl sensor based on FePt/ZnIn2S4 core-shell semiconductor nanostructures - Zeynali, Hossein (2020)
In this study, the FePt core, ZnIn2S4 shell and FePt-ZnIn2S4 core-shell nanostructures were successfully synthesized using solvothermal process. Temperature dependent hysteresis behavior of as-synthesized nanoparticles (NPs) FePt and FePt/ZnIn2S4 showed super paramagnetic response at 300 K and ferromagnetic properties with a coercive field (Hc) of 2830 Oe and 970 Oe at 2 K, respectively. Also, the blocking temperature (TB) estimating by the peak in ZFC curves was about 26 K for FePt and about 46 K for FePt/ZnIn2S4 NPs. After the identification process of nanostructure, using electrochemical methods, the behavior of FePt-ZnIn2S4 core-shell@PGE was studied in 0.1 M phosphate buffer solution (PBS) containing 5.0 mM [Fe(CN)6]3 /4 . The EIS complex plane plots showed a drastic change in the charge transfer resistance of the probe redox reaction as a function of UO2 2+ concentration. This behavior was used for construction of the calibration curve, and a linear range from 0.5 to 10.0 lM UO2 2+ with a detection limit of 71.7 nM.